Mali : Selected Issues. (IMF Staff Country Reports; Country Report, 2018)
This Selected Issues paper analyzes the impact of security crisis in Mali. The 2012 crisis has significant economic, social, and humanitarian impact, especially in the northern regions. The increase in security spending weighs on the budget and reduces space for priority spending. Persistent insecurity hinders investment and growth. The crisis resulted in the interruption and/ or disruption of learning activities in the northern part of the country, dangerously compromising the efforts of the Government of Mali and its partners to achieve Education For All. The security crisis has also slowed progress toward reducing poverty and achieving the Millennium Development Goals.